Hybrid versus in vitro fenestration for preserving the left subclavian artery in patients undergoing thoracic endovascular aortic repair with unfavorable proximal landing zone. (February 2020) - Wang, Maohua; Dong, Dianning; Yuan, Hai; Wang, Mo; Wu, Xuejun; Zhang, Shiyi; Zhong, Zhenyue; Jin, Xing; Zhang, Jingyong
Purpose: To compare hybrid and in vitro fenestration procedures for preserving the left subclavian artery in thoracic endovascular aortic repair (TEVAR) with unfavorable proximal landing zone. Methods: Retrospective comparison of data from 49 consecutive patients who underwent left subclavian artery revascularization during TEVAR by either hybrid or fenestration approaches from January 2015 to March 2018. Procedural duration, and 30-day rates of procedural success, mortality and complications (endoleaks, cerebral infarction, spinal cord ischemia, left arm ischemic symptoms, and delirium) were compared. Results: For hybrid procedure ( n = 32) vs. fenestration ( n = 17) groups, which were age and gender matched: procedural success rate was 100%, with significantly longer procedural duration (248.4 ± 40.9 vs. 60.6 ± 16.8 min; t = –22.653, P = 0.000) and similar 30-day complication rate (18.8% vs. 11.8%; χ 2 = 0.397, P = 0.529). At 12.7 ± 9.3 months' follow-up, there were no cases of death, spinal cord ischemia, or other complications in either group. Conclusions: In this retrospective, single-center comparison, both hybrid and in vitro fenestration approaches for reconstructing the left subclavian artery in TEVAR with unfavorable proximal landing zone appeared safe and effective, with shorter procedural duration for fenestration. Larger studies with longer term follow-up are warranted.